Search for proton radioactivity in 65As, 69Br and 77Y - Hourani, E. (1989)
A search for proton radioactivity in 65As, 69Br and 77Y, produced as residues of fusion reactions, was carried out at the Orsay Tandem accelerator. The residues were collected at the image point of the spectrometer Soleno and implanted into the gaseous medium of an ionization chamber which was also used to detect the radioactivity protons. No such protons have been observed in the energy range of 250–600 keV and in the half-life interval of 10 μs-100 ms, within a production cross section sensitivity of 1 μb.